X-ray diffraction data for "Kinetic Investigation of the Reaction of Dioxygen with the Copper(I) Complex [Cu(PimiPr2)(CH3CN)]CF3SO3 {PimiPr2 = Tris[2- (1,4-diisopropylimidazolyl)]phosphine}" - Becker, Jonathan; Lerch, Markus; Stumpf, Tim-Daniel J.; Miska, Andreas; Göttlich, Richard; Schindler, Siegfried; Justus Liebig University Giessen (My University, 2020)
Raw X-ray diffraction images for the publication Lerch, M., Weitzer, M., Stumpf, T.‐D.J., Laurini, L., Hoffmann, A., Becker, J., Miska, A., Göttlich, R., Herres‐Pawlis, S. and Schindler, S. (2020), Kinetic Investigation of the Reaction of Dioxygen with the Copper(I) Complex [Cu(PimiPr2)(CH3CN)]CF3SO3 {PimiPr2 = Tris[2‐(1,4‐diisopropylimidazolyl)]phosphine}. Eur. J. Inorg. Chem., 2020: 3143-3150. https://doi.org/10.1002/ejic.202000462. File format is the Bruker sfrm frame format. The data can be processed with the SAINT program by BRUKER AXS or using alternative and/or open source tools as XDS ( http://xds.mpimf-heidelberg.mpg.de/ ) together with sfrmtools ( https://homepage.univie.ac.at/tim.gruene/research/programs/conv/sfrmtools/ ) or FabIO ( Knudsen, E. B., Sorensen, H. O., Wright, J. P., Goret, G. & Kieffer, J. (2013). J. Appl. Cryst. 46, 537-539. ). FabIO provides the following information about the file format: "The bruker format uses 80 char lines in key : value format. In the first 512*5 bytes of the header there should be a HDRBLKS key, whose value denotes how many 512 byte blocks are in the total header. The header is always n*5*512 bytes, otherwise it wont contain whole key: value pairs. Data is stored in three blocks: 1. data (uint8) 2. overflow (uint32) 3. underflow (int32). The blocks are zero padded to a multiple of 16 bits.
Keywords: X-ray diffraction; Single crystal diffraction; Inorganic Chemistry; Coordination chemistry; Oxygen activation; ddc::540